Analyzing Economic Resilience of Rural Tourism in Indonesia Using Synthetic Composite Index - Nafiah Ariyani; Akhmad Fauzi (Faculty of Economic and Business, 2024)
Research Originality: This study used a new method, namely the Adjusted Mazziotta-Pareto Index (AMPI) to measure and categorize economic resilience using clustering analysis. In addition, the innovative method had not been previously applied to tourism resilience in Indonesia, making this study the first to measure tourism village resilience.Research Objectives: This study aimed to analyze economic resilience of tourism village destinations in Indonesia from 2019 to 2022 during the COVID-19 pandemic. Research Methods: The procedures were carried out using a quantitative method to determine resilience index of tourism village in Indonesia during the COVID-19 pandemic. Data were obtained from form management documents as well as 24 tourism villages across Java, Bali, and West Nusa Tenggara Provinces. Empirical Results: The results showed that the majority of villages were significantly impacted in the initial year of COVID-19, but were able to recover, demonstrating strong capacity and performance in recovering from the pandemic shock. In addition, economic aspects of capacity and performance showed high adaptability after the pandemic, indicating relative resilience to the shock. Implications: The results of this study could inform policies to enhance tourism village resilience in Indonesia. JEL Classification: O18, Z32, Z38How to Cite:Ariyani, N., & Fauzi, A. (2024). Analyzing Economic Resilience of Rural Tourism in Indonesia Using Synthetic Composite Index. Etikonomi, 23(2), 415 – 432. https://doi.org/10.15408/etk.v23i2.33355.